Strengthened the Concept of Numerical Literacy for Madrasah Ibtidaiyah Teachers Through Technical Guidance Follow-Up of Competency Assessment Results of Indonesian Students - Tri Astari (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2023)
The description of AKMI results needs to be conveyed to MI teachers so they can be used as a reference in developing numeracy literacy learning in class. In developing numeracy literacy learning, teachers need a good understanding and skills about numeracy literacy. So that it is necessary to strengthen the concept of numeracy literacy for Madrasah Ibtidaiyah teachers through technical guidance following up on the results of the Indonesian Student Competency Assessment. This activity consists of lectures, discussions, questions and answers with teachers; collaboration and discussion between teachers and other teachers; and demonstration/practice. The partners involved in this activity were Madrasah Ibtidaiyah teachers in Magelang Regency, Central Java, totalling 31 people. This activity ran smoothly, was interactive, and the participants were enthusiastic. Many participants took the pre-test and post-test, as many as 29 people. There was an increase of 27 people, although it has yet to occur significantly. In contrast, as many as two people are still at the same value—as many as 29 people have done peer teaching. Thus, there was an increase in participants' knowledge and skills regarding numeracy literacy.